2022
DOI: 10.1037/pha0000575
|View full text |Cite
|
Sign up to set email alerts
|

The validity of qualtrics panel data for research on video gaming and gaming disorder.

Abstract: Crowdsourced samples are increasing in popularity, particularly within psychological and addictive behaviors research. The trend has resulted in significant interest in the use of panel samples for the examination of behavioral and substance addictions. One newer panel platform, Qualtrics, has seen an increase in usage in recent years despite lack of research examining the validity of Qualtrics-produced data for addictive behaviors. The goal of the present study was to evaluate the validity of Qualtrics-obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Solutions with more than a single factor were not theoretically interpretable and presented substantial cross-loadings. In line with previous studies using panel recruitment for similar purposes, mean severity scores and proportions of individuals above the clinical cut-off in both samples of the current study were high, relative to samples obtained with other recruitment methods [50]. In other words, our factor analysis seems to be valid for the whole severity continuum and is not compromised by scores' range restriction.…”
Section: Discussionsupporting
confidence: 90%
“…Solutions with more than a single factor were not theoretically interpretable and presented substantial cross-loadings. In line with previous studies using panel recruitment for similar purposes, mean severity scores and proportions of individuals above the clinical cut-off in both samples of the current study were high, relative to samples obtained with other recruitment methods [50]. In other words, our factor analysis seems to be valid for the whole severity continuum and is not compromised by scores' range restriction.…”
Section: Discussionsupporting
confidence: 90%
“…To address these criticisms, Qualtrics have implemented techniques including a ‘prevent ballot box stuffing’, which uses internet browser cookies to prevent multiple survey completions and RelevantID, which ‘assesses participant metadata to detect fraudulent behaviors’ (Mullen et al, 2021, p. 223). Further, while not statistically representative, and to be interpreted with caution, research using non-probability online panels, including Qualtrics, have demonstrated similar results to probability-based panels that are population-based (Belliveau et al, 2022; Mullinix et al, 2015).…”
Section: Methodsmentioning
confidence: 96%
“…Moreover, studies have also demonstrated inconsistency in research outcomes when using university student samples, suggesting that student sampling methods can introduce significant problems in replicability (Peterson & Merunka, 2014). Despite such challenges to generalizability, psychology researchers continue to utilize student participant pools due to the convenience and facility of this recruitment procedure, its low cost, and its assumed low response bias (Belliveau et al, 2022; Landers & Behrend, 2015).…”
mentioning
confidence: 99%
“…Over the last decade, alternative convenience sampling methods have gained traction among social science researchers. These approaches involve crowdsourcing online panel data from platforms such as Qualtrics or Amazon’s Mechanical Turk (MTurk) which recruit a large and diverse pool of respondents who agree in advance to participate in survey research on various subjects and receive payment for participation through cash incentives, gift cards, or charitable contributions (Belliveau et al, 2022; Palmer & Strickland, 2016). The ability to recruit and include participants from a larger population pool (e.g., country wide) using online panel data may minimize barriers associated with convenience samples, thus offering data that are more representative and generalizable than that from student samples (Behrend et al, 2011; Landers & Behrend, 2015).…”
mentioning
confidence: 99%